Modulation of Drug Release: Exploring the Influence of Diisocyanate Variants on Polyurethane Matrix - Bauri S.; Tripathi S.; Garg K.A.; Maiti P. (My University, 2025)
Four different carrier systems based on polyurethane are designed for the controlled release of the model drug paclitaxel (PTX). The polyurethane (PU) carriers are characterized by Fourier transform infrared (FTIR), NMR, and UV-vis analyses, and their release behavior is investigated in phosphate buffer solution (PBS). The adjustment of different diisocyanate segments (2,4-toluene diisocyanate, 4,4′-methylene diphenyl isocyanate, 1,6-hexamethylene diisocyanate, and isophorone diisocyanate) facilitated the achievement of unique release profiles for the hydrophobic drug PTX. Notably, PU containing aromatic diisocyanate exhibits less than 20% drug release in PBS (pH 7.4), whereas those with aliphatic diisocyanates demonstrate a release of ∼80%, following a non-Fickian diffusion model. The observed differences in the release profiles are attributed to the intricate interplay among the polyurethane structure, hydrophobic/hydrophilic balance of PU, and drug-polymer interactions. From contact angle measurements, PU-I (IPDI-based PU) is found to be more hydrophilic. The combination of different diisocyanates with poly(tetramethylene glycol) influences the distribution and location of drugs within the polymer matrix, leading to diverse drug release mechanisms. Additionally, cellular adhesion experiments with SiHa cells validate the well-spread morphologies of the PU samples with greater adherence to the cell surfaces. FTIR analysis confirms the presence of the −NH- bond, which is in good agreement with the NMR spectra. These findings underscore the pivotal role of the segmental structure of polyurethane as a versatile tool for controlling drug release. © 2024 American Chemical Society.